Biosimilars, the journey has begun - Alba Martos-Rosa; Juan Enrique Martínez-de la Plata; Jose Antonio Morales-Molina; Anna Fayet- Pérez; Pedro José Acosta-Robles (Farmacia Hospitalaria)
According to the European Medicine Agency, a “biosimilar” is a biological medicinal product that contains a version of the active substance of an original biological medicinal product (reference or innovative medicinal product) that has been authorized in the European Economic Area. The similarity to the reference medicinal product in terms of quality, biological activity, safety and efficacy needs to be set on a comprehensive comparability basis. The generic standard approach (demonstration of bioequivalence with a reference medicinal product by appropriate bioavailability studies), which is applicable to a wide range of chemically derived medicinal products, is not sufficient to prove the similarity of biotechnology derived products due to their structural complexity. Furthermore, these biopharmaceuticals products, in comparison with the conventional ones, show a greater ability to activate the immune response. The evaluation of biosimilar medicines for authorisation purposes by the European Medicine Agency does not include recommendations on whether a biosimilar should be used interchangeably with its reference medicine. Substitution policies are, therefore, within the remit of the EU member states. In order to support pharmacovigilance monitoring, all appropriate measures should be taken to clearly identify any biological medicinal product with due regard to its brand name and batch number. The situation of the European Community and the regulatory framework have been developed since the first applications (growth hormone), almost a decade ago, until the recent advent (monoclonal antibodies). The introduction to the market of biosimilars have positive effects on competition by improving access to biological therapies